Creating an Interactive Procedure Text E- Module through Problem- Based Learning Approach by Using Canva - Surayawati, Sri Suci (STKIP PGRI Bandar Lampung, 2026)
This study aims to develop an interactive e-module for teaching procedure text by applying a Problem-Based Learning (PBL) approach and utilizing Canva as the design platform. The research focuses on enhancing students’ engagement and comprehension of procedure texts through interactive features and problem-solving activities integrated into the e-module. A Research and Development (R&D) method was employed, adapting the Borg and Gall model with stages of needs analysis, design, development, validation, revision, and implementation. Data were collected through expert validation sheets, questionnaires, and learning outcomes tests. The e-module was validated by two material experts and two media experts, showing very good criteria in terms of content accuracy, instructional design, interactivity, and visual presentation. The try-out was conducted with junior high school students, where results revealed that the e-module was practical, engaging, and effective in improving students’ understanding of procedure texts. The findings indicate that the e-module supports student-centered learning, promotes critical thinking, and provides visually appealing instructional materials. Furthermore, the integration of Canva enabled the creation of a user-friendly and interactive learning resource that fosters collaboration and active participation. Overall, the developed e-module serves as an innovative and feasible alternative tool to enhance students’ ability in comprehending and applying procedure texts within real-life contexts.